Kingdom of Swaziland : Assessment Letter for Multilateral and Bilateral Donors. (Policy Papers; Policy Paper, 2011)
This letter provides an assessment of recent macroeconomic developments in Swaziland and an update on the discussions between IMF staff and the Swaziland authorities. Swaziland faces a fiscal crisis caused by an 11 percent of GDP drop in revenue payments from the Southern African Customs Union (SACU) and one of the largest wage bills in Africa. In response, the authorities have put in place an ambitious Fiscal Adjustment Roadmap and requested IMF staff to monitor its implementation. The IMF Managing Director approved a Staff-Monitored Program with Swaziland on April 4, 2011, that seeks to start the necessary fiscal adjustment, while protecting education, health, and pro-poor spending and improving public financial management. Securing adequate financing in 2011/12 will be critical to avert a more severe fiscal situation.